A new corydiid cockroach with large holoptic eyes in Upper Cretaceous Burmese amber (Blattodea: Corydiidae: Euthyrrhaphinae). (April 2019) - Qiu, Lu; Wang, Zong-Qing; Che, Yan-Li
Abstract: A new corydiid cockroach, Magniocula apiculata gen. et sp. nov., is described and illustrated based on a well-preserved specimen in Upper Cretaceous Burmese amber. Magniocula is placed in the extant subfamily Euthyrrhaphinae based on the small pubescent body, large clypeus surpassing the distal border of the antennal sockets, and two spines at apex of the front femur. However, this new genus is unique among Euthyrrhaphinae for its holoptic eyes. This is the second corydiid species found in Cretaceous Burmese amber, which highlights the palaeodiversity of the family Corydiidae in the mid-Cretaceous.